Word order variation in non-verbal sentences in Egypt-Amarna letters - Westhuizen, J. P. van der (Journal for semitics, 2009)
The Egypt-Amarna letters, as part of the scope of the Amarna letters in general, a diplomatic correspondence, reflects a cosmopolitan "cuneiform" culture during the second millennium B.C., extending from the mountains east of Assyria and Babylonia into Asia Minor, providing rich evidence regarding the social and political history of Syria-Palestine in the fourteenth century B.C. and this is reflected, to a certain extent, in the Egypt letters. These letters are written in a Peripheral Akkadian (PA) dialect, a form of Western Peripheral Akkadian (WPA) dialect. The Egypt letters represent the correspondence of the pharaoh, concerning matters of importance to him, with recipients in Palestine and foreign countries. The administration of the Egyptian territories in Syria-Palestine is reflected in this correspondence. The structure of these letters, in all respects, is an important factor regarding and reflecting the relation between the pharaoh and the recipients, his subjects or otherwise. The aim of this paper, therefore, is to describe the application of word order in non-verbal sentences in the Egypt letters. The word order is important for conveying to the recipient, not only the meaning, but also the sense of the message the sender, the pharaoh, wishes to impress upon the recipient. In the Egypt-Amarna letters we have various syntagmas for non-verbal sentences, the word order of which may be established by the relative importance of the components of the sentence. This word order can be, either the "normal" SP[C] (subject, predicate [complement]) word order or, to emphasize a certain aspect, a deviation from the normal, as PS[C] to characterize either the progress of the action or the continuation of a situation, while SP[C] may be employed when a specific subject is to be introduced, either to highlight its identity or to mark the transition to a new subject. The variations in word order in non-verbal sentences are analysed according to the different types of sentence, such as equational, locative and existential sentences as well as the use of išû and bašû and the syntax of yānu/iānu. To assist in verifying the interpretation of these cases, the immediate contexts are taken into consideration. As basis for this study, to be a prolific study, Finley's study of word order in Syrian Akkadian (1979) and John Huehnergard's study On verbless clauses in Akkadian (1986), are consulted.